Pediatric Infectious Prepatellar Bursitis with Kingella kingae - Charles C. Pitts; Walter R. Smith; Michael J. Conklin (Case Reports in Orthopedics)
We present the first reported case of septic prepatellar bursitis with Kingella kingae in a 2-year-old female. Although it is a well-established cause of osteoarticular infections in the pediatric population, K. kingae has never been reported as the etiology for septic bursitis. A high index of suspicion is required for the diagnosis given that this organism is difficult to culture and isolate using standard laboratory methods. Our diagnosis was established through bursal fluid analysis, though oropharyngeal polymerase chain reaction (PCR) may be also be considered. Our case also builds upon prior literature suggesting that the pathophysiology of septic bursitis in children differs from that of the adult and may be more comparable to that of pediatric osteomyelitis. As an organism of increasing prevalence, K. kingae should remain high on the differential for osteoarticular or periarticular infections when cultures fail to isolate a distinct pathogen. Early diagnosis and a formal irrigation and debridement, if warranted, are crucial in preventing devastating complications of untreated septic bursitis.